Amelia lost : the life and disappearance of Amelia Earhart - Fleming, Candace (New York : Schwartz & Wade Books, 2011)
Traces the life of female aviator Amelia Earhart from her childhood to her final flight, discusses the extensive search for her and her missing plane, and includes photographs, maps, handwritten notes by Amelia, and sidebars.
Includes bibliographical references (p. 112-116) and index.
School Library Journal starred
Wilson's Children
Wilson's Junior High School
Book Links (A.L.A.), June 2011
Booklist, December 2010
Keywords: Earhart, Amelia, -- 1897-1937 -- Juvenile literature; Earhart, Amelia, -- 1897-1937.; Earhart, Amelia, -- 1897-1937.; Air pilots -- United States -- Biography -- Juvenile literature; Women air pilots -- United States -- Biography -- Juvenile literature; Air pilots; Women -- Biography; Air pilots -- Biography; Women -- Biography